Konglomerasi Media dan Konstruksi Praksis Demokrasi Pasca Rezim Orde Baru: Sebuah Refleksi Awal - Nyarwi Nyarwi (Program Studi Ilmu Komunikasi, 2008)
After the post New Order Regime Soeharto, the Indonesian mass media industries have been developing their self as media conglomeration model. Some group of media industries manufactured their symbolic reality based on the power of commoditization of their conglomeration at local level and national level. Almost of them synergized their business networking industries of broadcasting industries, newspaper industries and also multimedia industries as a part of new media competitions. This paper will examine and reflected the impact of media conglomeration of mass media industries on practical construction of Indonesia democracy after Post New Order Soeharto. The media duty as empowering of the public interest is the missing important thing among the owners of media industries, journalist, politician and civil society.